PEMBERDAYAAN KADER KESEHATAN DALAM SOSIALISASI SISTEM RUJUKAN JKN DI PUSKESMAS GOMBONG - Shafitri Nire Pangestika; Eka Oktavia (ICON Publisher, 2026)
The National Health Insurance Program aims to improve equitable access to health services through a tiered referral system. However, many people still do not understand the referral mechanism, so they often go directly to advanced health facilities without first visiting primary health facilities. This community service activity aims to increase public understanding of the National Health Insurance referral system and to strengthen the role of health cadres in delivering health information. The implementation method was carried out through health education activities for community members visiting the Bayan Community Health Center in Purworejo Regency. The activities were conducted using lectures, discussions, and question-and-answer sessions with simple, easy-to-understand language, supported by basic educational media. The participants totaled 50 people, consisting of housewives, fathers, pregnant women, adolescents, and parents of toddlers. The analysis technique was descriptive, based on evaluating participants’ understanding after the health education sessions. The results showed that participants were enthusiastic, and most were able to better understand the flow of the health service referral system. Around 95 percent of participants demonstrated improved comprehension of health service procedures and the correct referral steps. This activity indicates that direct health education through counseling can enhance community health literacy and support the proper utilization of health services in accordance with the applicable referral system.